Effect of Different Plant Extracts on Microbial Population in The Frozen African Catfish (Clarias gariepinus) Semen: Plant Extracts’ Impact on Microbial Count in Frozen Catfish Semen - Secer, Faik Sertel; Yavas, Ilker; Cantekin, Zafer; Bozkurt, Yusuf; Korkmaz Yavas, Tugba; Atanasoff, Alexander (Cellular and Molecular Biology, 2023)
Fish sperm cryopreservation has been attempted on roughly freshwater and marine species since 1953. This study sought to assess the potential of various plant extracts to function as natural antimicrobial agents in the frozen semen of African catfish (Clarias gariepinus). Diluted sperm was packaged in 0.25ml straws and left for 10min equilibration at 4°C. Following equilibration, the straws were exposed to liquid nitrogen vapor for 10 min and plunged into the liquid nitrogen (-196°C) and then thawed in a water bath at 35°C for 20s. Sperm samples were put into sterile 1.5 ml tubes immediately after thawing and the microbial count was detected with classical microbiological culture method. In the results of microbiological analyses, these tree plant extracts especially Echinacea purpurea were found highly effective for decreasing bacterial contamination levels of African catfish (C. gariepinus) semen. These plant extracts may have the potential for antibacterial effect, and they can be useful for the dilution of semen.